Analysis of Joint Responsibility Contracts in The Perspective of Muamalah Syariah in Dharma Sejahtera Village-Owned Enterprises (BUMDESMA) - Edhi Satria, Resma; Sujatna, Yayat (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2025)
The purpose of this study is to understand the process of the tanggung renteng program and to examine and analyze its implementation from the perspective of Islamic muamalah in the BUMDesma Dharma Sejahtera, Kalitidu. This research is a qualitative study using a descriptive-analytical approach. The research was conducted at the Joint Village-Owned Enterprise (BUMDesma) Dharma Sejahtera, located on Jalan Raya Kalitidu No. 139, Kalitidu Subdistrict, Bojonegoro Regency, East Java, in 2024. Data collection techniques used include interviews, participatory observations, and documentation. Based on the results of the study and discussion, it can be concluded that the practice of the tanggung renteng system in the BUMDesma Dharma Sejahtera, Kalitidu, Bojonegoro, includes group formation, credit application, verification and socialization, evaluation meetings, contract signing, loan disbursement, installment payments collected by the group leader, and monitoring and evaluation of loan usage. The existence of the tanggung renteng system benefits the community, particularly in fostering a sense of mutual assistance among group members. From the perspective of Islamic muamalah, the tanggung renteng system at the BUMDesma Dharma Sejahtera involves a multi-contract approach, combining mudharabah and kafalah contracts. Its implementation is in accordance with Islamic legal provisions.